Comprehensive investigation of sources of misclassification errors in routine HIV testing in Zimbabwe. Issue 4 (21st April 2021) - Gregson, Simon; Moorhouse, Louisa; Dadirai, Tawanda; Sheppard, Haynes; Mayini, Justin; Beckmann, Nadine; Skovdal, Morten; Dzangare, Janet; Moyo, Brian; Maswera, Rufurwokuda; Pinsky, Benjamin A; Mharakurwa, Sungano; et al.
Abstract: Introduction: Misclassification errors have been reported in rapid diagnostic HIV tests (RDTs) in sub‐Saharan African countries. These errors can lead to missed opportunities for prevention‐of‐mother‐to‐child‐transmission (PMTCT), early infant diagnosis and adult HIV‐prevention, unnecessary lifelong antiretroviral treatment (ART) and wasted resources. Few national estimates or systematic quantifications of sources of errors have been produced. We conducted a comprehensive assessment of possible sources of misclassification errors in routine HIV testing in Zimbabwe. Methods: RDT‐based HIV test results were extracted from routine PMTCT programme records at 62 sites during national antenatal HIV surveillance in 2017. Positive‐ (PPA) and negative‐percent agreement (NPA) for HIV RDT results and the false‐HIV‐positivity rate for people with previous HIV‐positive results ("known‐positives") were calculated using results from external quality assurance testing done for HIV surveillance purposes. Data on indicators of quality management systems, RDT kit performance under local climatic conditions and user/clerical errors were collected using HIV surveillance forms, data‐loggers and a Smartphone camera application (7 sites). Proportions of cases with errors were compared for tests done in the presence/absence of potential sources of errors. Results: NPA was 99.9% for both pregnant women (N = 17224) and male partners (N = 2173). PPA was 90.0% (N = 1187) and 93.4% (N = 136) for women and men respectively. 3.5% (N = 1921) of known‐positive individuals on ART were HIV negative. Humidity and temperature exceeding manufacturers' recommendations, particularly in storerooms (88.6% and 97.3% respectively), and premature readings of RDT output (56.0%) were common. False‐HIV‐negative cases, including interpretation errors, occurred despite staff training and good algorithm compliance, and were not reduced by existing external or internal quality assurance procedures. PPA was lower when testing room humidity exceeded 60% (88.0% vs. 93.3%; p = 0.007). Conclusions: False‐HIV‐negative results were still common in Zimbabwe in 2017 and could be reduced with HIV testing algorithms that use RDTs with higher sensitivity under real‐world conditions and greater practicality under busy clinic conditions, and by strengthening proficiency testing procedures in external quality assurance systems. New false‐HIV‐positive RDT results were infrequent but earlier errors in testing may have resulted in large numbers of uninfected individuals being on ART.